2008
DOI: 10.1378/chest.07-1007
|View full text |Cite
|
Sign up to set email alerts
|

Trends in End-of-Life ICU Use Among Older Adults With Advanced Lung Cancer

Abstract: Background-There is increasing concern about the appropriateness of intensive medical care near the end of life in ICUs throughout the United States. As a result of hospice expansion in the 1990s, we hypothesized that ICU use decreased over time in older adults with advanced lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 20 publications
6
63
0
3
Order By: Relevance
“…However, the appropriateness of administering chemotherapy close to death should be carefully evaluated [52], given that receiving chemotherapy at the EOL is not influenced by the cancer's responsiveness to chemotherapy [41] and that the more intense use of chemotherapy by medical oncologists does not prolong survival [56]. Furthermore, the cumulative use of chemotherapy may take a negative toll, leading to more complications, subsequent frequent ER visits and admissions and ICU care, longer hospitalizations, and death in the hospital, as evident in our own study (data not shown) and in other studies [3,57,58]. Closing the gaps in knowledge, attitudes, and beliefs could eliminate the disparities in EOL care across physician specialty lines.…”
Section: Resultssupporting
confidence: 58%
“…However, the appropriateness of administering chemotherapy close to death should be carefully evaluated [52], given that receiving chemotherapy at the EOL is not influenced by the cancer's responsiveness to chemotherapy [41] and that the more intense use of chemotherapy by medical oncologists does not prolong survival [56]. Furthermore, the cumulative use of chemotherapy may take a negative toll, leading to more complications, subsequent frequent ER visits and admissions and ICU care, longer hospitalizations, and death in the hospital, as evident in our own study (data not shown) and in other studies [3,57,58]. Closing the gaps in knowledge, attitudes, and beliefs could eliminate the disparities in EOL care across physician specialty lines.…”
Section: Resultssupporting
confidence: 58%
“…In addition to rapidly aging demographics, there has also been increasing intensity of care for the elderly and terminally ill in the past decades. 65,66 Between 1997 and 2003, there was a 57 % age-adjusted increase of HD initiation in octogenarians and nonagenarians. 7 This trend contributes to runaway costs that threaten the solvency of Medicare.…”
Section: Justice: Patients' Rights and Distributive Justicementioning
confidence: 99%
“…폐 암 환자의 5년 생존율은 평균 15% 정도이며 수술이 불가 능한 폐암 환자의 5년 생존율은 5%에도 미치지 못하 고 있다 3,4 . 이와 같이 매우 나쁜 예후에도 불구하고 폐암 이 진행되어 사망이 임박한 환자뿐만 아니라 폐색전증, 심근경색증, 폐렴 등의 질환이 동반된 폐암 환자는 병원에 입원하게 된다 1,5 .…”
Section: 서 론unclassified